2007
DOI: 10.1021/ed084p1225
|View full text |Cite
|
Sign up to set email alerts
|

Calculating Interaction Energies Using First Principle Theories: Consideration of Basis Set Superposition Error and Fragment Relaxation

Abstract: The use of computational chemistry tools has become prevalent in a wide variety of research areas. Many researchers are using computational chemistry as an additional tool to explore and gain insight into the problems they are researching. As such it is important to educate future scientists in the capabilities and proper implementation of theoretical tools. In this article we explain a difficult aspect of computational chemistry: calculating accurate interaction energy by correcting for basis set superpositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…23 This quantity characterizes the energy change of [NbF 7 ] complex in the system (without taking into account the complex interaction energy with the environment) compared to that of the free [NbF 7 ] complex. In terms of the BSSE theory (BSSE -basis set superposition error), 24,25 the E com energy is the energy of relaxation. electrode is presented in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…23 This quantity characterizes the energy change of [NbF 7 ] complex in the system (without taking into account the complex interaction energy with the environment) compared to that of the free [NbF 7 ] complex. In terms of the BSSE theory (BSSE -basis set superposition error), 24,25 the E com energy is the energy of relaxation. electrode is presented in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The BSSE is especially prominent in systems with intermolecular hydrogen-bonds, [51][52][53][54][55][56][57] and is thus expected to influence the RDF of methanol. It has been shown that the calculation of the BSSE corrections can change their potential energy curves and surfaces, [58][59][60][61][62] and can alter the bond distances.…”
mentioning
confidence: 99%
“…Values E int and E dist were derived by employing the Boys-Bernardi counterpoise scheme, which calculates electronic energies of catalyst and substrate fragments from previously optimised geometries. 3,51,52 As detailed in Scheme 11, deconstructed directing group binding electronic energies for CF 2 H-containing substrate 4b were assessed. Consistent with the D(DG bind ) free energy calculations, moving from catalyst 2a to 2d progressively improves the overall binding electronic energy for the sulfonamide over the competing pyrazole (E bind ; blue).…”
Section: Kinetic Analysis Of Intramolecular Directing Group Chemoselectivity Across the Evolving Catalyst Seriesmentioning
confidence: 99%